2020
DOI: 10.1177/1120700020917939
|View full text |Cite
|
Sign up to set email alerts
|

Limited need for screening of metal-on-metal hip resurfacing patients beyond 10 years of follow-up

Abstract: Background: National and international guidelines lack consistency on how to screen metal-on-metal (MoM) hip arthroplasty patients for adverse reactions to metal debris (ARMD). Long-term outcomes of MoM hip arthroplasty are scarce, hindering further development of such guidelines. We present the clinical, radiological and ARMD status of 158 cases of hip resurfacing with >10 years follow-up. Methods: A prospective analysis of a cohort of 298 consecutive hip resurfacing procedures was performed at a single in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…6,12,[23][24][25] Other studies report that in asymptomatic patients with normal blood metal ion levels (< 2 μg/l) and normal ultrasound imaging, the risk of progression of ultrasound findings is small within five years of initial assessment. 26,27 Besides the local effect of metal debris, there are concerns about possible systemic toxic effects of elevated levels of metal ions found in large-diameter MoM THA. 28,29 Risk factors for elevated blood levels are malposition, taper issues, and prosthesis design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,12,[23][24][25] Other studies report that in asymptomatic patients with normal blood metal ion levels (< 2 μg/l) and normal ultrasound imaging, the risk of progression of ultrasound findings is small within five years of initial assessment. 26,27 Besides the local effect of metal debris, there are concerns about possible systemic toxic effects of elevated levels of metal ions found in large-diameter MoM THA. 28,29 Risk factors for elevated blood levels are malposition, taper issues, and prosthesis design.…”
Section: Discussionmentioning
confidence: 99%
“…Our study adds evidence to the hypothesis that elevated blood metal ion levels, as reported by several institutions, have poor discriminant ability in predicting pseudotumour formation. 26,27 In a study on MoM hip resurfacing, it was noted that the discriminatory capacity of cobalt alone was similar to cobalt and chromium combined, suggesting the limited utility of chromium ion levels. 34 It was recommended that the decision for revision surgery cannot be made based on blood metal ion values.…”
Section: Discussionmentioning
confidence: 99%
“…However, their implants were 2nd-generation Metasul implants and thus not directly comparable to our study ( 19 ). It has been suggested that beyond 10 years from surgery the appropriate follow-up interval for MoM hip resurfacing patients could be 5 years ( 4 ). Based on our data and these previous data we suggest that 5-year measurement interval for asymptomatic ReCap-M2a-Magnum patients may be sufficient in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Reito et al have previously reported similar findings in their study of 154 ASR patients ( 25 ). It has been suggested that routine MARS-MRI imaging after 10 years of MoM hip implantation might not be beneficial ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation